Royal taxation in fourteenth century France : the development of war financing, 1322-1356 - Henneman, John Bell (Princeton legacy library., 1971)
The capture of the French king John II at Poitiers in 1356 marked the end of royal taxation as a temporary, wartime expedient and its beginning as an annual assessment. John Henneman's detailed treatment of war financing in the period immediately preceding, from 1322 to 1356, is the first volume in a proposed study of royal finances in France during the fourteenth century. Mr. Henneman has chosen a chronological approach to his subject in order to show how the evolving theory and practice of taxation were affected by these turbulent years of war and negotiation, political faction and dynastic feuds, social and economic change. Mr. Henneman discusses the king's requirements for money over and above his normal revenues, the methods he used to raise the funds, the responses of his subjects, and the changes these procedures made in the development of French institutions. His study is based largely on unpublished sources, especially the manuscripts found in French provincial archives. As the royal financial records in Paris have been dispersed or destroyed, these manuscripts arc of particular importance.Originally published in 1971.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.